Tagalog Language Maintenance and Shift Among the Filipino Community in New Zealand - Umali, Ronalyn (Auckland University of Technology, 2016)
The purpose of this study is to investigate the factors that affect the attitudes and behaviours of Filipino migrants regarding their ethnic language maintenance in New Zealand. The research design was guided by a social psychological perspective, focusing on the attitudes and behaviours of 15 participants based on particular situations and social interactions. Qualitative data were collected through one-on-one interviews and informal fieldwork observations. Interviews were recorded, transcribed, coded, and analysed using Thematic Analysis. Results showed that the majority of participants have positive attitudes towards ethnic language maintenance in the Filipino-New Zealand community. Their positive attitudes were influenced by their constant involvement with the Filipino ethnic group, good relationships with members of the host society, and their views on heritage language as core to their ethnic identities. It was also found that the participants tended to fulfil the linguistic expectations of their family members and the wider Filipino community by using the ethnic language often. However, despite the participants’ positive attitudes, findings revealed that the use of the Tagalog language is not maintained among second-generation Filipino migrants. Regardless of their desire to pass on their ethnic language, most participants with New Zealand-born children use English as their main language of communication at home. In cultural events and gatherings, it was also found that Filipino adults would use English when speaking with Filipino children, but would switch back to Tagalog when conversing with other Filipino adults. Tagalog is only used by the first generation and those who have already acquired it, while the younger generation is left isolated from the language. There is a clear contradiction between the participants’ positive attitudes and their behaviours towards ethnic language maintenance. This suggests that English will most likely be the main language of the succeeding Filipino-New Zealand generations. Without proper attention and diligent use of Tagalog among Filipino children, a language shift seems inevitable among the second and third-generation Filipino migrants.
Keywords: Language maintenance; Language shift; Filipino community; Tagalog; Attitude and behaviour; Community languages in New Zealand